Acute rheumatic fever in south-east of Turkey: clinical features and epidemiological evaluation of the patients over the last 25 years. (2nd August 2020) - Erdem, Sevcan; Demir, Fadli; Ayana, Mustafa; Canan, Oguz; Okuducu, Yankı Kaan; Arslan, Alev; Kucukosmanoglu, Osman; Özbarlas, Nazan
Abstract: This study evaluates clinical and epidemiological features of acute rheumatic fever using the data of last 25 years in our hospital in south-east of Turkey. The medical records of 377 patients with acute rheumatic fever admitted to Pediatric Cardiology Department of Çukurova University during 1993–2017 were retrospectively analysed. Two hundred and six patients were admitted between 1993 and 2000, 91 between 2001 and 2008, and 80 between 2009 and 2017. The largest age group (52%) were between 9 to 12 years of age and approximately two-thirds of the patients presented in the spring and winter seasons (62.8%). Among the major findings, the most common included carditis 83.6% (n = 315), arthritis at 74% (n = 279), Sydenham's chorea at 13.5% (n = 51), and only two patients (0.5%) had erythema marginatum and two patients (0.5%) had subcutaneous nodule. Carditis was the most common manifestation observed in 315 patients (83.6%). The most commonly affected valve was the mitral valve alone (54.9%), followed by a combined mitral and aortic valves (34%) and aortic valve alone (5.7%). Of the patients with carditis, 48.6% (n = 153) had mild carditis, of which 45 had a subclinical. Sixty-two patients (19.7%) had moderate and 100 patients (31.7%) had severe carditis. At the follow-up, 2 patients died and 16 patients underwent valve surgery. Twenty-eight (7.4%) patients' valve lesions were completely resolved. Conclusion: Although the incidence of acute rheumatic fever decreased, it still is an important disease that can cause serious increases in morbidity and mortality rates in our country.